1987
DOI: 10.1159/000199533
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Retrograde Pancreatography and Exocrine Pancreatic Function

Abstract: The incidence of pancreatitis has been increasing during the last decennium paralleling a rapid enhancement in alcohol consumption. For many years, diagnostic criteria of chronic pancreatitis were exclusively based on the estimation of the exocrine pancreatic function. New valuable information is provided from endoscopic retrograde pancreaticography (ERP) and pancreatic ultrasonography. In a consecutive series of patients with chronic alcoholism changes in the pancreatogram were demonstrated in approximately 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous studies suggested that pancreatic functional impairment may be present in the case of normal pancreatograms, and that a normal pancreatic duct on ERP does not exclude exocrine pancreatic insufficiency.3 4 10 17 19 35 In a study entailing a large number of patients, almost all of a subgroup of patients with normal pancreatic duct morphology and functional impairment were found to have only slight pancreatic insufficiency.19 In our patients, normal pancreatograms always correlated with normal exocrine function. In contrast, morphological duct changes were always associated with impaired pancreatic function, and the extent of pancreatic insufficiency depended on the severity of the morphological changes.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies suggested that pancreatic functional impairment may be present in the case of normal pancreatograms, and that a normal pancreatic duct on ERP does not exclude exocrine pancreatic insufficiency.3 4 10 17 19 35 In a study entailing a large number of patients, almost all of a subgroup of patients with normal pancreatic duct morphology and functional impairment were found to have only slight pancreatic insufficiency.19 In our patients, normal pancreatograms always correlated with normal exocrine function. In contrast, morphological duct changes were always associated with impaired pancreatic function, and the extent of pancreatic insufficiency depended on the severity of the morphological changes.…”
Section: Discussionmentioning
confidence: 56%
“…1,2,5,6 Pancreatographic findings and evaluation of the exocrine function of the pancreas have been shown to correlate well primarily in advanced chronic pancreatitis. 2,[7][8][9][10][11][12] However, evaluation of pancreatic exocrine function using only structural changes has been found inadequate. 7,11 Phospholipase A 2 , one of the pancreatic digestive enzymes, has not been included as an enzyme marker in duodenal intubation tests.…”
Section: Introductionmentioning
confidence: 99%